Stéréotype et information télévisuelle - Catherine Ghosn (Communication)
The goal of this work is to treat the role of stereotyping as a discursive strategy in televised news programs. Between the theoretical position and language practices, the study focuses on the mechanisms of both usage and construction of stereotypes. Inscribed in media discourse analysis, we examine the discursive practice of stereotyping in the televised news program which was broadcast by France 2 from January to June, 2000 at 1:00 p.m. and at 8:00 p.m. each day. By placing ourselves on a bipolar axis (model/experience) we reveal the putting into place which stereotypes undergo in communicational and televisual practices.